Editorial Board Reflections on Formative Books and Other Media. Issue 1 (1st December 2022) - Parille, Ken; Kidd, Kenneth; Mechling, Jay; Cann, Victoria; Morris, Edward W.
Abstract: Reading Characters, People, and Properties In this piece, I reflect on superhero comic books I read in my childhood and adolescence, noting that as I collected and read stories featuring the character known as the Silver Surfer, I slowly began to realize that the character's traits, as established in the first comic in which he appeared, seemed to change in comics published later. In searching for explanations for these changes, I began to pay attention to a comic's credits, recognizing that different writers and artists understood the character in different ways and often felt no obligation to maintain a consistent approach. I eventually realized that a comic's credits sometimes misrepresented the labor invested by each of the story's creators. This long process led to an ongoing interest—in both my writing and teaching—in the ways that our interpretation of a story and its characters can be enriched by understanding the conditions under which it was produced. Books of the Heart What might reflecting on favorite books from our childhood tell us about our past and current selves? This short meditation on that question first considers reading memoirs and experiments in rereading, and then reviews some favorite books from the author's own childhood, speculating on their appeal and potential significance for identity consolidation. The Fantasy of the Boy Scout Handbook Born and raised in Miami Beach, Florida, I opened my new Boy Scouts of America Handbook for Boys in the summer of 1956, at age 11, in anticipation of moving from the Cub Scouts to the Boy Scouts that fall. I found in those pages a fantasy that moved me deeply, a romantic fantasy of hiking and camping in the wilderness with a band of boy buddies. That fantasy has deep roots in fiction for boys and in books like the Handbook, appealing to the boy's desire to escape the surveillance and control of adults and to fashion a community of "lost boys" in a wilderness setting ideal for strong male bonding in friendship. "I Never Had Any Friends Later on Like the Ones I Had When I Was Twelve. Jesus, Does Anyone?": Reflections on Learning about Boyhood through Stand by Me This piece offers reflections on the 1986 movie Stand by Me, drawing on some of the main themes and contextualizing them in relation to my own childhood as a girl growing up in the 1990s. I reflect on how in my rewatch of the movie, I was struck by the ways that the class positions of the boys echoed my own experiences of transition and liberation through education. I also reflect on the significance of seeing boys cry and be scared—feelings that the boys at my school were policed out of performing in public. Boy Genius: Reflections on Reading The Great Brain Based on reflection and analysis of a formative childhood text, this essay disentangles the relationship between reading, intelligence, and masculinity. The author argues that although reading fiction appears to encourage empathy, books written specifically for boys may contain detrimental messages about masculinity. The analysis reveals that the popular Great Brain series reinforces notions of whiteness, ableism, and masculine superiority. These messages are reinforced by the books' emphasis on pragmatic "genius" and the savior trope in boyhood.